2019
DOI: 10.3390/molecules24162977
|View full text |Cite
|
Sign up to set email alerts
|

VOC Profiles of Saliva in Assessment of Halitosis and Submandibular Abscesses Using HS-SPME-GC/MS Technique

Abstract: Halitosis and submandibular abscesses are examples of mouth-related diseases with the possible bacterial origin. Salivary volatile organic compounds (VOCs) are potential biomarkers of them, once they can be addressed as metabolites of bacterial activity. Healthy patients (n = 15), subjects with submandibular abscesses located in fascial deep space (n = 10), and subjects with halitosis (n = 5) were enrolled in the study. Saliva samples were subjected to headspace solid-phase microextraction (HS-SPME) and gas ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…However, they can have an equally important role. It is confirmed by studies using gas chromatography-mass spectrometry [29,32,44]. In the paper of Monedeiro et al, in the persons with IOH, 85 volatiles, were detected, and the most predominant classes of malodor compounds were alcohols and ketones.…”
Section: Volatile Compoundsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, they can have an equally important role. It is confirmed by studies using gas chromatography-mass spectrometry [29,32,44]. In the paper of Monedeiro et al, in the persons with IOH, 85 volatiles, were detected, and the most predominant classes of malodor compounds were alcohols and ketones.…”
Section: Volatile Compoundsmentioning
confidence: 76%
“…In this group, in comparison to healthy persons, an increased number of volatile sulfur compounds and esters was observed. Simultaneously, authors found ten VSCs substances: methyl thioacetate, dimethyl disulfide, dimethyl trisulfide, dimethyl tetrasulfide, dimethyl pentasulfide, dimethyl sulfone, allyl thiocyanate, allyl isothiocyanate, S-methyl pentanethioate, and thiolan-2-one [44]. In other studies, in halitosis patients, the 30 most abundant volatile compounds in the oral cavity belonged to alkanes or alkane derivatives, therein methyl benzene, tetramethyl butane, and ethanol [45].…”
Section: Volatile Compoundsmentioning
confidence: 87%
“…CE-MS offers high-analyte resolution and a small volume of sample for injection (1–20 nL) [ 52 , 53 ]. GC-MS is a gold standard for the analysis of volatiles and it is, relatively, a simpler technique than LC-MS, more cost effective and with reduced matrix effect enabling to quantify compounds in picograms and identification using easy-accessible reference libraries [ 27 , 28 , 29 ]. It is also possible to separate and analyze semi-volatiles, for example when using solvent extraction as the sample preparation technique.…”
Section: Studies On Colorectal Cancer Metabolic Biomarkersmentioning
confidence: 99%
“…Among the small metabolites, volatile organic compounds (VOCs) are metabolic products that can elicit diversified patterns that may represent very specific biochemical ongoing processes in the organism. Volatiles’ profiles have been studied in the context of several diseases, especially in exhaled breath, using GC-based analyses [ 25 , 26 , 27 , 28 ]. In this context, GC analysis is extremely relevant, because it encompasses the group of VOC metabolites, which cannot be properly assessed by LC.…”
Section: Introductionmentioning
confidence: 99%
“…Halitosis, also known as oral malodor, usually refers to the unpleasant gas that occurs in the oral cavity, nasal cavity, sinuses, or pharynx during breathing . It is caused by various volatile molecules including volatile sulfur compounds (VSCs), aromatic compounds, amines, and so on .…”
Section: Introductionmentioning
confidence: 99%